2003
DOI: 10.1007/s00284-002-3957-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the High-Virulence Clone of Group B Streptococci by Using a Probe Containing a Putative Aldolase Gene

Abstract: A high-virulence clone (HVC) was proposed as causing much of the morbidity and mortality when a collection of group B Streptococcus (GBS) isolates was examined by multi-locus enzyme electrophoresis. HVC isolates could be further distinguished by their inability to grow at 40 degrees C, and a temperature-sensitive aldolase was identified as responsible for this characteristic. In the present study, the HVC was sought in a collection of 57 GBS isolates by hybridization with a probe containing a putative aldolase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In addition, we detected the genes for virulence factors Lmb, CylE, and ScpB in all our isolates and other virulence genes in variable percentages, among them the major virulence adhesin coded by the hvgA gene. These findings suggest that GBS hypervirulent clones are circulating in the population studied, as previously described in a sample of GBS isolates from Mexico City [ 56 ]. Although we did not find evidence of GBS disease, it illustrates the importance of knowing the pathogenic characteristics of GBS populations circulating in different regions.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, we detected the genes for virulence factors Lmb, CylE, and ScpB in all our isolates and other virulence genes in variable percentages, among them the major virulence adhesin coded by the hvgA gene. These findings suggest that GBS hypervirulent clones are circulating in the population studied, as previously described in a sample of GBS isolates from Mexico City [ 56 ]. Although we did not find evidence of GBS disease, it illustrates the importance of knowing the pathogenic characteristics of GBS populations circulating in different regions.…”
Section: Discussionsupporting
confidence: 78%
“…Sudden temperature upshift may induce temporary growth inhibition of bacterial cells and rearrangement of gene expression directed towards survival, including for GBS strains (5,(14)(15)(16). The present study demonstrated that temperature changes may influence GBS survival within endothelial cells.…”
Section: Discussionmentioning
confidence: 74%